The influence of mineral exports on the variability of tropical deforestation - Sunderlin, William D.; Wunder, Sven (2000)
Previous studies of deforestation have focused on agriculture, population and migration, timber exploitation, macroeconomic policies and geographic factors to explain the variability of deforestation rates among countries. This study tests the hypothesis that countries with a high proportion of petroleum or non-petroleum mineral exports in total exports experience a relatively low deforestation rate because of macroeconomic 'Dutch disease' effects. Bivariate and multivariate analyses provide preliminary support for the hypothesis, although giving little insight on how precisely mineral exports might exert their influence on forest cover. One reason for the limited utility of these methodologies is that they do not adequately explain the various effects of mineral windfalls that go beyond the Dutch disease's 'core model'. Future research must attempt to understand these effects, which include: levels of funding for agriculture, roads, and directed settlement; agricultural protectionism; levels of rural poverty, urbanisation, and consumer demand; the site-level effects of mineral extraction; and the variability of state autonomy.